2015
DOI: 10.1007/s11581-015-1558-0
|View full text |Cite
|
Sign up to set email alerts
|

Control of calcium oxalate morphology through electrocrystallization as an electrochemical approach for preventing pathological disease

Abstract: Artículo de publicación ISIPathological crystallization of calcium oxalate (CaOx) inside the urinary tract is called calculi or kidney stone (Urolithiasis). CaOx exhibits three crystalline types in nature: CaOx monohydrate COM, dihydrate COD and trihydrate COT. COD and COM are often found in urinary calculi, particularly COM. Electrocrystallization has been recently used to perform oriented crystallization of inorganic compounds such as Ca-salts. Although many mineralization methods exist, the mechanisms invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 41 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…In Figure 6, it is possible to observe diffraction peaks that are attributable to both COD as COM crystals. However, more intense peaks, detected at 2θ, such as 15 • , 25 • , 30 • and 31 • , correspond to crystal planes {1 0 1}, {2 1 1}, {2 0 2} and {0 2 0} of COM crystals respectively, which confirm what is observed by the above analysis [43,[71][72][73][74]. In general, the use of this kind of functionalized DSPF film as a solid organic template could contribute to understanding the mechanisms underlying the formation of biologically important minerals, such as pathological urinary crystal forms, and it is kinetic on surface deposition.…”
Section: Resultssupporting
confidence: 84%
“…In Figure 6, it is possible to observe diffraction peaks that are attributable to both COD as COM crystals. However, more intense peaks, detected at 2θ, such as 15 • , 25 • , 30 • and 31 • , correspond to crystal planes {1 0 1}, {2 1 1}, {2 0 2} and {0 2 0} of COM crystals respectively, which confirm what is observed by the above analysis [43,[71][72][73][74]. In general, the use of this kind of functionalized DSPF film as a solid organic template could contribute to understanding the mechanisms underlying the formation of biologically important minerals, such as pathological urinary crystal forms, and it is kinetic on surface deposition.…”
Section: Resultssupporting
confidence: 84%
“…This is due to the highly conductive capacity of the ITO substrate, which conducts the current previously established in the program at −890 mV in the electrochemical solution, allowing the reduction of oxygen, which generates an increase in the pH value that favors the conversion of bicarbonate to carbonate [39]. It is well known that the ITO substrate represents a conductive material with optoelectronic applications due to its good optical transparency, high conductivity, and electrochemical stability [40]. CaCO 3 crystals obtained with EC method in the presence and absence of Chi-P onto ITO substrate were compared and evaluated through the measurement of current (mA) at different times (min).…”
Section: Resultsmentioning
confidence: 98%
“…Bone is a hierarchical composite material that consists of collagen and minerals. [7c,8,106] Previous studies have suggested that the crystalline relationship between collagen and minerals in the formation of bone is as follows: The calcium and phosphate ions are transferred to minerals within the collagen . Two primary models have been proposed for bone mineralization: Nanocrystals nucleate from solution in the presence of collagen, and matrix vesicles assemble ions from the ECM.…”
Section: Applications Of Biomineralizationmentioning
confidence: 99%
“…Two primary models have been proposed for bone mineralization: Nanocrystals nucleate from solution in the presence of collagen, and matrix vesicles assemble ions from the ECM. [1a,7b,109] Rodriguez et al demonstrated that osteoblasts concentrate calcium and phosphate ions to form ACP, which then permeates into the collagen fibrils and crystallizes into HAP …”
Section: Applications Of Biomineralizationmentioning
confidence: 99%
See 1 more Smart Citation